Goodnight moon - Brown, Margaret Wise, 1910-1952.; Hurd, Clement, 1908-1988. (New York : Scholastic, 1982)
Goodnight to each of the objects in the great green room: goodnight chairs, goodnight comb, goodnight air.
Keywords: Bedtime -- Juvenile fiction; Rabbits -- Juvenile fiction; Fiction